Wind Gusts Associated with Tornado-Scale Vortices in the Tropical Cyclone Boundary Layer: A Numerical Simulation - Liu, Qingyuan; Wu, Liguang; Qin, Nannan; Song, Jinjie; Wei, Na (Frontiers in Earth Science, 2022)
It has been demonstrated that the tornado-scale vortex (TSV) is one of the fine-scale structures associated with extreme updrafts in the tropical cyclone boundary layer (TCBL), but the relationship between surface wind gusts and TSVs is still unclear. In this study, the one-second model output simulated in the Weather Research and Forecast (WRF) model with the large eddy simulation (WRF-LES) is used to investigate the relationships between TSVs and surface wind gusts. Results show that surface wind gust factors in the regions where TSVs are prevalent are significantly larger than those in other regions. 88% of the maximum gust factors associated with TSVs (vertical velocity larger than 20 m s−1) are larger than 1.25 (gust factors larger than 1.25 account for only 1% of the 1-min gust factors in the TC inner core), and the mean maximum 1-min gust factor associated with a TSV is larger than 1.3, while the mean 1-min gust factor in the TC inner core is only 1.1. The surface gust factors associated with TSVs in tropical cyclone eyewall can reach about 1.8, which can cause severe surface wind hazards. This study suggests that potential risk will increase in the regions where TSVs are prevalent because of the large wind gusts and gust factors. Finer real-time observations are needed to monitor the evolution of TSVs for improving the operational TC-related surface gust warnings.